The Effect of Ecological Approaches on Tactical Performance in Volleyball: A Systematic Review - Rodríguez-Gutiérrez Amparo; Conejero Suárez Manuel; Moreno Domínguez Alberto (Applied Sciences, 2025)
Interventions based on improving athletes’ adaptive capacity to game environment conditions have been widely developed in sports science. The objective of this study was to systematically review the scientific literature on interventions and applications, from an ecological perspective, for the tactical performance of volleyball players. A systematic search was conducted in five electronic scientific databases in accordance with PRISMA guidelines: Web of Science (WOS), PubMed (Medline), Scopus, SportDiscus and Google Scholar. A total of eight studies met the inclusion criteria, all published after 2014. The risk of bias and main characteristics of the articles in different contexts were assessed. Particular attention was paid to recording data related to the characteristics of manipulation or the timing of the intervention. The results showed that these approaches influenced tactical variables in volleyball game situations. In this sense, short-session interventions with small-sided games and modifications of structural elements aid athletes’ self-regulation in different environments. Furthermore, results show that this approach allows for improvements in individual and collective tactical behavior. Based on the data analyzed, we recommend the use of ecological tasks, based on representative and modified practices that promote player adaptation, as a methodological tool in the volleyball training process.